1962
DOI: 10.1128/aem.10.5.452-457.1962
|View full text |Cite
|
Sign up to set email alerts
|

Graphical Procedure for Comparing Thermal Death of Bacillus stearothermophilus Spores in Saturated and Superheated Steam

Abstract: SHULL, JAMES J. (Wilmot Castle Co., Rochester, N. Y.) AND ROBERT R. ERNST. Graphical procedure for comparing thermal death of Bacillus stearothermophilus spores in saturated and superheated steam. Appl. Microbiol. 10:452-457. 1962-The thermal death curve of dried spores of Bacillus stearothermophilus in saturated steam was characterized by three phases: (i) a sharp initial rise in viable count; (ii) a low rate of death which gradually increased; and (iii) logarithmic death at maximal rate. The first phase was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1963
1963
1971
1971

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…than activated spores, a time delay would result before all remainiing viable spores were activated and equally susceptible to heat, and the logarithmic portion of the death curve would extrapolate to a point in excess of the direct counit. The latter situation was observed by lialvorson (1958) and inferred in the report of Shull and Ernst (1962). Shull and Ernst (1962) demonstrated that heat activation can be responsible for a signiificant portion of the initial lag in the thermal death curves of spores of Bacillus stearothermophilus, but it was still niot clear how much of the lag could be attributed to heat activation, and whether the death of the spores obeyed first-order kinetics.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…than activated spores, a time delay would result before all remainiing viable spores were activated and equally susceptible to heat, and the logarithmic portion of the death curve would extrapolate to a point in excess of the direct counit. The latter situation was observed by lialvorson (1958) and inferred in the report of Shull and Ernst (1962). Shull and Ernst (1962) demonstrated that heat activation can be responsible for a signiificant portion of the initial lag in the thermal death curves of spores of Bacillus stearothermophilus, but it was still niot clear how much of the lag could be attributed to heat activation, and whether the death of the spores obeyed first-order kinetics.…”
mentioning
confidence: 77%
“…The latter situation was observed by lialvorson (1958) and inferred in the report of Shull and Ernst (1962). Shull and Ernst (1962) demonstrated that heat activation can be responsible for a signiificant portion of the initial lag in the thermal death curves of spores of Bacillus stearothermophilus, but it was still niot clear how much of the lag could be attributed to heat activation, and whether the death of the spores obeyed first-order kinetics. We have re-examined this system in an effort to resolve three questions.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…These data suggest that there may be differences between wet and dry heat survivor curves. Shull et al (1962) found that the survivor curve of dried B. stearothermophilus spores heated in saturated steam had three phases: (1) an initial rise; (2) a low rate of death which increased slowly;…”
Section: Introductionmentioning
confidence: 99%